Comparison of different decellularization methods for human anterior lens capsules - Jianfeng Yu; Pengfei Li; Kai Fan; Jiawei Luo; Huaijin Guan (BMC Ophthalmology)
Abstract Background Human anterior lens capsules (ALCs) have great potential in the treatment of multiple eye diseases, including corneal ulcers, glaucoma, age-related macular degeneration and macular holes. ALCs are also regarded as promising scaffolds for various ocular cells. Here, we investigated different decellularization methods for removing lens epithelial cells (LECs) that adhered to ALCs. Methods Human ALCs were treated with various solutions, including 2% lidocaine, 10% sodium chloride, 50% glucose and sterile water. Trypan blue and alizarin red (TB-AR) staining, H&E staining and hydroxyproline assays were used to assess the degree of decellularization. The impacts of acellular ALCs on cell viability and cell-tissue interaction were investigated in vitro. Results These findings revealed that 2% lidocaine, 10% sodium chloride, 50% glucose, and sterile water had the capacity to decellularize ALCs at 37 °C. The structure of ALCs in all decellularization groups was similar to that of intact ALCs. The effects of 10% sodium chloride and sterile water on decellularization were significantly better than those of 2% lidocaine and 50% glucose. The H&E staining revealed that the different decellularization methods maintained the integrity of the lens capsular structure. Compared with sterile water, 10% sodium chloride preserved a better level of hydroxyproline. The ALCs in the 10% sodium chloride-treated group and the sterile water-treated group were shown to be suitable for cell adhesion in vitro. Conclusion This study identified two optimal decellularization methods for acellular ALCs: using 10% sodium chloride and using sterile water. The obtained acellular ALCs could be promising scaffolds for ocular cells. In addition, acellular ALCs do not need resterilization and may be directly used for autologous lens capsule transplantation in clinical applications.